Downregulation of Checkpoint Protein Kinase 2 in the Urothelium of Healthy Male Tobacco Smokers - Breyer, Johannes; Denzinger, Stefan; Hartmann, Arndt; Otto, Wolfgang (Urologia Internationalis, 2016)
With this letter to the editor we present for the first time a study on CHEK2 expression in normal urothelium of healthy male smokers, former smokers and non-smokers. We could show a statistically significant downregulation of this DNA repair gene in current smokers compared to non-smokers, suggesting that smoking downregulates CHEK2 in normal urothelium, probably associated with an early step in carcinogenesis of urothelial bladder carcinoma.
EVALuna2:6921